2019
DOI: 10.1101/644724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allelic polymorphism shapes community function in evolving Pseudomonas aeruginosa populations

Abstract: AbstractPseudomonas aeruginosa is an opportunistic pathogen that chronically infects the lungs of individuals with cystic fibrosis (CF) by forming antibiotic resistant biofilms. Emergence of phenotypically diverse isolates within CF P. aeruginosa populations has previously been reported, however, the impact of heterogeneity on social behaviors and community function is poorly understood. Here we describe how this heterogenei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 93 publications
(139 reference statements)
1
6
1
Order By: Relevance
“…We have shown that, contrary to the trade-off hypothesis, virulence does not necessarily increase even when the restriction of transmission potential is removed. In fact, evolution was not reproducible in the three independent selection lines, in contrast to a previous study that showed P. aeruginosa evolution was highly reproducible in vitro [73], further highlighting the importance of factoring host-specific variables such as immune response in predictions of virulence. Our study also adds to the breadth of knowledge on P. aeruginosa adaptations in chronic wounds, showing that while P. aeruginosa employs similar adaptive strategies, i.e.…”
Section: Discussioncontrasting
confidence: 98%
“…We have shown that, contrary to the trade-off hypothesis, virulence does not necessarily increase even when the restriction of transmission potential is removed. In fact, evolution was not reproducible in the three independent selection lines, in contrast to a previous study that showed P. aeruginosa evolution was highly reproducible in vitro [73], further highlighting the importance of factoring host-specific variables such as immune response in predictions of virulence. Our study also adds to the breadth of knowledge on P. aeruginosa adaptations in chronic wounds, showing that while P. aeruginosa employs similar adaptive strategies, i.e.…”
Section: Discussioncontrasting
confidence: 98%
“…The concept of population phenotype is related to the frequencies and distribution of relevant alleles in bacterial populations, which can shape community functions and influence clinical outcomes (Azimi et al, 2020). In this work, we demonstrate how the dynamics of multiple and changing antibiotic pressures, together with higher mutation rates, resulted in high allelic variations of the PDC β-lactamase in a diversified resistant clonal population that originally evolved from a susceptible ancestral infecting strain.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional environment is increasingly appreciated as a major selective pressure, which motivated development of an artificial sputum medium that approximates concentrations found in patients with CF and produces similar growth phenotypes and transcriptional responses as actual sputum (20)(21)(22). Evolution experiments with P. aeruginosa have been conducted in this medium to identify beneficial mutations in particular conditions, including antibiotic pressure (23), biofilm lifestyle (24), and presence of mucins (23,25). Several observations are consistent across these studies, particularly the rapid diversification of biofilm, motility, and colony phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Several observations are consistent across these studies, particularly the rapid diversification of biofilm, motility, and colony phenotypes. Mutations in certain genes have also been identified repeatedly including lasR, wsp, and flagella synthesis genes (23,24,26,27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation